Changes in Aortoiliac Anatomy After Elective Treatment of Infrarenal Abdominal Aortic Aneurysms with a Sac Anchoring Endoprosthesis. Issue 1 (January 2016) - Boersen, J.T.; Schuurmann, R.C.L.; Slump, C.H.; van den Heuvel, D.A.F.; Reijnen, M.M.P.J.; ter Mors, T.G.; Vahl, A.C.; de Vries, J.P.P.M.
Abstract : Objective: Endovascular aortic sealing (EVAS) with the Nellix endosystem (Endologix, Irvine, CA, USA) is a new concept to treat infrarenal abdominal aortic aneurysms (AAAs). By sealing the aneurysm, potential endoleaks may be avoided. Early results of EVAS are good, but no data have been published regarding peri-procedural changes in aortoiliac anatomy. In this study, 27 consecutive patients who underwent elective EVAS repair of an AAA were reviewed. Method: Specific AAA (diameter, length from renal arteries to aortic bifurcation, supra- and infrarenal neck angulation, AAA volume, thrombus volume, and flow lumen volume), and iliac artery characteristics (length, angulation, location of most severe angulation with reference to the origin of the common iliac artery) were determined from pre- and post-procedural reconstructed computed tomography angiograms. Results: No type I or II endoleaks were seen at 30 day follow up. Total AAA volume, suprarenal and infrarenal angulation, as well as aortic neck diameter did not change significantly post-EVAS. AAA flow lumen increased significantly (mean difference −4.4 mL, 95% CI 2.0 to −8.6 mL) and AAA thrombus volume decreased (mean difference 3.2 mL, 95% CI 2.0 to −1.1 mL). AAA length (125.7 mm vs. 123.1 mm), left common iliac artery length (57.6 mm vs. 55.3 mm), and right and left maximum iliac artery angulation (right 37.4° vs. 32.2°; left: 43.9° vs. 38.4°) were reduced significantly and the location of maximum angulation was further from the iliac artery origin post-EVAS, suggesting slight straightening of the aortoiliac anatomy. Conclusion: Most aortoiliac anatomic characteristics remained unchanged post-EVAS. Filling of the endobags to a pressure of 180 mmHg may lead to lost thrombus volume in some patients, probably because liquid is squeezed into lumbar or the inferior mesenteric artery. The absolute differences in pre- and post-EVAS aortoiliac lengths were small, so pre-operative sizing is accurate for determining stent length.